SNR-Enhanced Fast BOTDA Combining Channel Estimation Technique With Complementary Pulse Coding - Can Zhao; Ming Tang; Ruolin Liao; Hao Wu; Songnian Fu (IEEE Photonics Journal, 2018)
We have implemented a BOTDA that combines channel estimation and complementary coding technique for high performance distributed sensing. The use of OFDM-modulated probe reduces the measurement time sharply compared to the classical frequency sweeping technique. Meanwhile, the complementary coding provides a higher SNR of the sensing system, which further reduces the measurement time by mitigating averaging. The method of combining the channel estimation technique and complementary coding is theoretically analyzed. It has been demonstrated that the pulse coding scheme can benefit both the Brillouin gain spectrum (BGS) and Brillouin phase spectrum (BPS). Experiments are carried out using 512-bit codewords on a 10-km single-mode fiber with a spatial resolution of 25 m. The complex BGS distribution is measured within 2 ms, with a BFS uncertainty of 1.1 and 0.6 MHz for BGS and BPS, respectively.